MESSAGE FRAMING AND INVOLVEMENT IN INFLUENCING ATTITUDES TOWARDS ORGANIC PRODUCTS - Andhy Setyawan (Journal of Management and Business, 2014)
The research reveals the role of message framing and involvement in influencing attitudes towards organic products. The research data obtained through experimental techniques were attended by 180 students. The results showed that the effect of the negative message framing is more effective in subjects with a high level of involvement, while the influence of a positive message framing is more effective in subjects with low involvement.